Recent advances in synthetic approaches for medicinal chemistry of C-nucleosides - Temburnikar, Kartik; Seley-Radtke, Katherine L. (Beilstein Journal of Organic Chemistry, 2018)
C-nucleosides have intrigued biologists and medicinal chemists since their discovery in 1950's. In that regard, C-nucleosides and their synthetic analogues have resulted in promising leads in drug design. Concurrently, advances in chemical syntheses have contributed to structural diversity and drug discovery efforts. Convergent and modular approaches to synthesis have garnered much attention in this regard. Among them nucleophilic substitution at C1' has seen wide applications providing flexibility in synthesis, good yields, the ability to maneuver stereochemistry as well as to incorporate structural modifications. In this review, we describe recent reports on the modular synthesis of C-nucleosides with a focus on D-ribonolactone and sugar modifications that have resulted in potent lead molecules.
Keywords: C-nucleosides; convergent synthesis; modular synthesis